Experiences of diasporic Muslim women: a study of Mohja Kahf's and Umm Zakiyyah's works - Saiful Bahri, Aisyah; Hasan, Md. Mahmudul (IIUM Press, International Islamic University Malaysia, 2017)
Muslim women are often portrayed and perceived in a negative light in the dominant Western narrative, especially in the post-9/11 era. Western misconceptions of Islam have proliferated a distorted identity of Muslims. For the Muslim diaspora, struggling with hyphenated identity, this phenomenon has further complicated their image as Muslims. Such epistemic injustices have greater impact on Muslim women who are often the primary target for harassment and violence in the street.This study examines the process of identity formation of contemporary diasporic Muslim women living in the USA. The two works chosen are Mohja Kahf’s The Girl in the Tangerine Scarf (2006) and Umm Zakiyyah’s Realities of Submission (2008). The discussion is based on each writer’s representation of the Muslim self with various themes including challenging the Western stereotypes of Muslims, confronting the identity crisis as well as overcoming cultural and religious differences.